Cultural capital and health literacy among urban communities in Malaysia: A cross-sectional study - Nurul Izyan Husna Ibrahim; Abdul Hafiz Ab Rahman; Azlina Abdullah; Shamarina Shohaimi (PLoS ONE, 2026)
Health literacy is an important determinant of health outcomes, yet many approaches continue to emphasize individual cognitive skills while giving limited attention to the sociocultural resources that shape how people engage with health information. This study examined the association between cultural capital and multiple dimensions of health literacy among urban communities in Malaysia. A cross-sectional study was conducted among 325 adults residing in selected urban communities in Ipoh, Perak. A cluster-based approach was used to identify study locations, followed by community-based convenience recruitment within selected clusters. Cultural capital was assessed across embodied, objectified and institutionalized dimensions, while health literacy was measured using the validated HLS-M-Q18 instrument, which captures access, understanding, evaluation and application of health information. All constructs demonstrated good internal consistency (Cronbach alpha = 0.822 to 0.931). Spearman’s rank correlation was used for bivariate analysis due to non-normality, while multiple linear regression estimated the independent contribution of each form of cultural capital to each health literacy domain. Cultural capital was significantly associated with all dimensions of health literacy (p < 0.001). Institutionalized cultural capital was the strongest predictor of access (β = 0.298, p < 0.001) and understanding (β = 0.305, p < 0.001), whereas embodied cultural capital was the only significant predictor of evaluation (β = 0.537, p < 0.001) and the strongest predictor of application (β = 0.359, p < 0.001). Cultural capital explained between 28.2% and 41.9% of the variance across outcomes. Differences were also observed across education and income levels. These findings indicate that health literacy is not determined by access to information alone but is shaped by broader social and cultural resources. Public health interventions should therefore move beyond information provision and strengthen the experiential and contextual capacities that enable individuals to evaluate and apply health information in everyday life.